2018
DOI: 10.1111/ajag.12528
|View full text |Cite
|
Sign up to set email alerts
|

Key issues to consider and innovative ideas on fall prevention in the geriatric department of a teaching hospital

Abstract: Falls in hospital are common and up to 70% result in injury, leading to increased length of stay and accounting for 10% of patient safety-related deaths. Yet, high-quality evidence guiding best practice is lacking. Fall prevention strategies have worked in some trials but not in others. Differences in study setting (acute, subacute, rehabilitation) and sampling of patients (cognitively intact or impaired) may explain the difference in results. This article discusses these important issues and describes the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
7
0
2
Order By: Relevance
“…The visual instruction was strengthened by scenes of broken bones to arouse emotional memory since emotional scenes are better remembered than ordinary ones. 22…”
Section: Silent Video Clips With Simple Fall Prevention Messages Reduce Fallsmentioning
confidence: 99%
“…The visual instruction was strengthened by scenes of broken bones to arouse emotional memory since emotional scenes are better remembered than ordinary ones. 22…”
Section: Silent Video Clips With Simple Fall Prevention Messages Reduce Fallsmentioning
confidence: 99%
“…12 Quasi-experimental (pre-and postintervention) studies have reported a decrease in the fall rate following the addition of an educational video to existing fall prevention programmes. [13][14][15] Studies evaluating the effectiveness of educational videos often exclude individuals with cognitive impairment. [16][17][18] We designed an educational video that encouraged patients to seek help when ambulating.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported to reduce the fall rate among inpatients in an acute geriatric ward (30% of them had dementia). 14 We aimed to examine whether our fall prevention educational video performs better than the standard verbal fall prevention education for individuals with cognitive impairment in terms of retention of the fall prevention message and reduction in fall rate.…”
Section: Introductionmentioning
confidence: 99%
“…Trials investigating this approach for people after stroke found no increase in adverse events including falls and no increase in caregiver burden. 9 , 10 However, these risks are important for older people with multimorbidity 3 , 13 and need consideration.…”
Section: Introductionmentioning
confidence: 99%
“…The hazards of hospitalisation, including bed rest and injurious falls, can make transitioning home difficult for older adults with multimorbidity. [1][2][3] Programs such as Transition Care in Australia 4 and Intermediate Care in the United Kingdom 5 aim to support older people with time and therapy to facilitate their return to community living. Physiotherapy can facilitate recovery of physical function 6 but the amount of therapy received by patients in transitional programs is often low.…”
Section: Introductionmentioning
confidence: 99%